Respuesta :

Answer: 2x³ - 3x² + 7x + 8

Step-by-step explanation:

   Sum = 4x³ - 3x² + 3x + 8 + (6x³ - 7x² + 4x) + (-8x³ + 7x²)     [write the terms as given by the quetion and group like terms]

⇒ Sum = (4x³ + 6x³ - 8x³) + (- 3x²  - 7x² + 7x²) + ( 3x + 4x) + 8   [complete the addition of like terms]

∴ sum = 2x³ - 3x² + 7x + 8

Answer:

2x³ - 3x² + 7x + 8

Step-by-step explanation:

We require to add

4x³ - 3x² + 3x + 8 + 6x³ - 7x² + 4x - 8x³ + 7x² ← collect like terms

= (4 + (6 - 8)x³ + (- 3 - 7 + 7)x² + (3 + 4)x + 8

= 2x³ + (- 3)x² + 7x + 8

= 2x³ - 3x² + 7x + 8

ACCESS MORE